Computer-Assisted Modeling and Examination of Protein-Molecule Complexes - Klaus Müller (CHIMIA)
Three applications of the new Roche Interactive Molecular Graphics system are outlined. They include (i) the computer-assisted fitting of various brodimoprim derivatives into the active sites of L.casei and E.coli dihydrofolate reductases (DHFR), (ii) the modeling of complexes of L.casei DHFR with its natural substrate and reaction product, dihydrofolate and tetrahydrofolate, respectively, and (iii) the docking of the cofactor NADPH into the binary complex of E.coli DHFR and methotrexate.